Obtaining nano-structured composite materials based on three antimony oxides (sol-gel method) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article examines the mode of obtaining gelation (xerogel) from a composite substance soap solution, antimony trioxide (Sb2O3), PVA (polyvinyl acetate) and H2O in a liquid medium using a complex metric method. For effective complex formation, an electric mixer (dissolver) was used with mechanical stirring for 40 minutes, resulting in a ratio of a multicomponent substance in accordance with the formula МР0,2х·Sb6,0х· ПВА1,5Х ·H209,8x (where x=0,2:6,0:1,5:9,8). Studies of these complex formation reactions are based on the interaction of organic complexons with metal ions. Thus, the “sol-gel” process involves hydrolysis at a certain temperature range, 48-52°C, and the mechanical actions of the latter lead to further polymerization with the formation of a viscous resin (gel). Crystallization of the “sol-gel” compound was determined at a temperature of 140-150°C, held for 1.0 hour. The resulting compound type of complex substance is called antimony polyvinyl acetate.
Keywords: sol-gel, xerogel, airgel, colloid, coagulation, polymerization, complex formation, antimony trioxide, dissolver